The Influence of School’s Culture and Principal’s Academic Supervision on the Teaching Quality of High School Teachers - Rachmawati, Ririn; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2024)
The research aims to analyze the influence of school culture, academic supervision, and school culture on the teaching quality of high school teachers in Banyuasin I District, Banyuasin Regency. This research was conducted at one of the high schools in Banyuasin I District using quantitative methods. The population was 121 teachers, using probability sampling techniques. A sample of 93 people was determined using the Slovin formula. The results of the research show that school culture and principal supervision have a positive effect on the teaching quality of high school teachers in Banyuasin I District. The combination of school culture and academic supervision contributes to the overall quality of teacher teaching.